A phase I/II study to evaluate safety, tolerability and immunogenicity of Hillchol®, an inactivated single Hikojima strain based oral cholera vaccine, in a sequentially age descending population in Bangladesh. Issue 32 (22nd July 2021) - Chowdhury, Fahima; Ali Syed, Khalid; Akter, Afroza; Rahman Bhuiyan, Taufiqur; Tauheed, Imam; Khaton, Fatema; Biswas, Rajib; Ferdous, Jannatul; Al Banna, Hasan; Ross, Allen G.; Mc Millan, Nigel; Sharma, Tarun; et al.
Abstract: Background: The World Health Organization (WHO) recommends the use of oral cholera vaccines (OCVs) as part of an integrated control program, both in highly endemic settings and during cholera epidemics. The available and internationally recommended WHO-prequalified OCVs (Dukoral, Shanchol, Euvichol) contain multiple heat and formalin-killed V. cholerae strains of Inaba and Ogawa serotypes. MSD Wellcome Trust Hilleman Laboratories Pvt. Ltd. in technical collaboration with University of Gothenburg, Sweden has developed a new single strain OCV, Hillchol. This vaccine consists of formaldehyde-inactivated whole cell El Tor V. cholerae O1 bacteria engineered into the Hikojima serotype for stable expression of both the Ogawa (AB) and Inaba (AC) LPS antigens on the bacterial surface. We evaluated the safety and immunogenicity of this novel and potentially much less expensive OCV in comparison with Shanchol. Methods: We conducted a randomized, non-inferiority, age-descending clinical trial of OCV (Hillchol vs. Shanchol) in the Mirpur area of Dhaka city from July 2016 to May 2017. This study was carried out in three different age cohorts (1–<5, 5–17 and ≥18 years old). Two doses of vaccine were given at 14 days intervals to 560 healthy participants. Findings: No serious adverse events were reported. There were no significant differences in the rates of adverse events between the test vaccine (Hillchol) and the comparator (Shanchol) group. Serum vibriocidal antibody responses in all age groups combined were comparable for all the O1 Ogawa (59% vs. 67%; 90% CI of difference: −14.55, −0.84) and Inaba (70% vs. 71%; 90% CI of difference: −7.24, 5.77) serotypes, showing that the Hillchol vaccine was non-inferior to Shanchol. This new vaccine was also non-inferior to Shanchol in the different age strata. Conclusion: The safety and immunogenicity profile of the new OCV Hillchol is comparable to Shanchol in persons residing in a cholera-endemic setting. ClinicalTrials.gov number: NCT02823899.